The Role Of Guidance And Counseling Services In Improving Students' Discipline At MTS Miftahul Huda - Diana Eva Lux Putri (Jolly Journal of English Education, 2025)
This research aimed to describe the role of guidance and counseling (GC) services in improving students’ discipline at MTs Miftahul Huda. Student discipline was a vital aspect that supports the success of the educational process. However, undisciplined behaviors such as being late to school, not completing assignments, and other rule violations are still common. This research used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results showed that guidance and counseling services play a significant role in fostering and directing students to understand the importance of discipline through informational services, individual counseling, and group guidance. Furthermore, collaboration between school counselors, homeroom teachers, and parents also supports the success of this program. In conclusion, guidance and counseling (GC) services made a positive contribution to improving student discipline at MTs Miftahul Huda.